(untitled) (Research, Society and Development, 2021)
The adolescence is a period of heterogeneous growth that marks the transition from childhood to adulthood, being associated with the development of sexual behavior, which may lead to an increased risk of sexually transmitted infections due to unprotected sex. The purpose of this study is to analyze the scientific production on the vulnerabilities of adolescents to sexually transmitted infections. The research was based on the methods of an integrative review of the literature, which allows for the incorporation of evidence, a selection of studies was carried out in health databases such as: Lilacs, Scielo and Scopus. The inclusion criteria were: scientific articles, published between the years of 2013 to 2020. The collection period occurred in June of the year 2020. The research showed that the adolescents are in an individual vulnerability process to be used methods of preventing STIs in an irregular manner, such as condoms, associated with a lack of information on issues related to sexuality in adolescence such as: body; sex; genre; prevention of STIs. It was reported on the importance of the family to guide adolescents about sexuality and health, as well as the nurse for being a professional who act on educational actions in health in the health services. There is a need to expand and strengthen prevention actions among adolescents within schools, as proposed by the Health in School Program, involving students, teachers, families and the community in general. Strengthen educational health actions by building strategies that reach adolescents to reduce infections in this group.